Diet quality and obesity in women of reproductive age in Northern Tanzania: a cross-sectional study - Bliznashka, Lilia; Azupogo, Fusta; Reynolds, Elise; Arnold, Charles D.; Hess, Sonja Y.; Kinabo, Joyce; Jeremiah, Kidola; Malindisa, Evangelista; Olney, Deanna K.; Ruel, Marie T. (MedRxiv, 2025)
Background: Obesity is an increasing problem among women of reproductive age (WRA) in Tanzania. Objective: We described WRA's nutritional status by socio-demographic factors and assessed associations with diet quality. Methods: We analysed baseline data from a cluster-randomised controlled trial in Arusha and Kilimanjaro regions (n=2,415). Diet was assessed using a quantitative 24-hour recall. We calculated the Global Diet Quality Score (GDQS; 0-49), with higher scores indicating healthier diet. General obesity was defined as body mass index (BMI)>=30 kg/m2; morbid obesity as BMI>=35 kg/m2; and central obesity as: waist circumference (WC)>=80 cm, WC>=88 cm, waist-to-hip ratio (WHR)>=0.85, waist-to-height ratio (WHtR)>=0.50, and WHR>=0.85 or BMI>=30 kg/m2. We tested associations between diet quality and nutritional status using generalised linear models controlling for age and sociodemographic factors and tested interactions to assess differential associations by age groups. Results: The prevalence of general obesity was 25.1%, morbid obesity 8.4%, and central obesity 48.2-71.6% depending on the definition. Mean GDQS was 20.9 (SD 3.9). General and central obesity were more prevalent among women who were older, less educated, had light physical labour occupations, were in the highest wealth quintile, and lived in more urbanised villages and in more food secure households. Higher GDQS was associated with lower risk of morbid obesity: risk ratio (RR) 0.97 (95% CI 0.94, 1.00). Higher GDQS was also associated with 0.25-0.27 kg/m2 lower BMI, 0.54-0.66 cm lower WC, and 0.53-0.58 cm lower hip circumference in women 30-49 years of age. Conclusion: Better diet quality emerged as a protective factor for morbid obesity and for other obesity measures among women 30-49 years of age. Our study suggests that interventions to improve diet quality in Tanzania should target women in their thirties and forties and those with lower physical activity and higher education, food security, and wealth to maximise effectiveness.